(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article reveals the role and social status of women in society. Information is given that a woman in modern society has a completely different status and vocation, she has other values and needs that make us reconsider our views on the female role in today’s world. The historiography of sources considering the women’s issue is also given